Creation of Cervical Cancer Risk Factor Score Card in order to Know the Risk Score for Cervical Cancer in Women of Reproductive Age by Conducting Self-Assessment - A’im Matun Nadhiroh; Budi Santoso; Suhatno; Windhu Purnomo; Heru Santoso Wahito Nugroho (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Cervical cancer is the second most common malignancy among various cancers in the genetalia of women, and often occurs at reproductive age. Purpose: The purpose of this study is to create a cervical cancer risk factor score card in order to know the risk score for cervical cancer in women of reproductive age by conducting self-assessment. Methods: The design of this research was cross-sectional, with 81 patients as respondents. Data were collected through filling out a questionnaire, then analyzed using Mc Nemar Test and ROC curve. Findings: Obtained a cut-off point 11 with a sensitivity value of 93.8%, a specificity of 90.9%. The results of testing the validity of the score card obtained results with an accuracy value of 92.6%, with a significant value of 0.000, which means there was a relationship between the scorecard and the diagnosis of cervical cancer. Conclusion: The score card can be used as a self-assessment in the hope that it can increase women to perform early detection of cervical cancer.